Building Healthy Digital Generation: Parenting Education to Reduce Online Game Addiction Among Children in Leuwikaret Village - Gunawan Wiradharma; Mario Aditya Prasetyo; Irla Yulia; Khaerul Anam (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
This article aims to analyze the impact of digital parenting education activities in improving parents’ digital competencies and preventing online game addiction among children in Leuwikaret Village. The background of this community service activity (PkM) is based on the high intensity of digital technology use among children, which is not accompanied by adequate parental digital literacy, thereby increasing the risk of digital addictive behaviors. This study employs a quantitative approach with a one-group pretest–posttest design involving 40 respondents, who are parents with school-aged children. Data were collected through a Likert-scale questionnaire measuring understanding of digital parenting concepts, the risks of game addiction, and its impact on child development. The findings indicate a significant improvement across all indicators of digital parenting competencies, with a large effect size. The highest increase was observed in the understanding of psychological and social impacts, suggesting that context-based educational approaches are more effective. Additionally, there was a decrease in the need for supplementary materials, indicating an increase in parents’ self-efficacy. Another finding reveals a gap in basic literacy among some respondents, which affects their comprehension process. This article concludes that digital parenting education effectively enhances parents’ digital competencies at the cognitive level and has the potential to serve as a preventive strategy against digital addiction. Future efforts require sustained interventions and more robust research designs to measure long-term impacts on changes in children’s behavior.